Update on medical therapy for male LUTS - Radomski, Sidney B. (Canadian Urological Association Journal, 2014)
The medical management of lower urinary tract symptoms (LUTS) is aimed at addressing voiding and storage symptoms in patients with benign prostate hyperplasia (BPH) symptoms with or without an overactive bladder (OAB). Current available options for BPH include the alpha-blockers, 5-alpha reductase inhibitors, and phosphodiesterase type 5 inhibitors. For OAB, options include antimuscarinics, with or without an alpha-blocker, the beta-3-adrenergic agonist mirabegron, and the synthetic diuretic desmopressin. With the availability of numerous options and combinations available for the treatment of LUTS, individual patient assessment is the key to optimal symptom control and management of adverse effects.